Wavelets na quantificação de tumores de fígado em exames contrastados de tomografia computadorizada - Rodrigues, Bruna Teiga [UNESP]; Alvarez, Matheus [UNESP]; Souza, Rafael Toledo Fernandes [UNESP]; Romeiro, Fernando Gomes [UNESP]; Pina, Diana Rodrigues de [UNESP]; Trindade, André Petean [UNESP]; Miranda, José Ricardo de Arruda [UNESP] (My University, 2012)
This paper presents an original methodology of liver tumors segmentation, based on wavelet transform. A virtual phantom was constructed with the same mean and standard deviation of the intensity of gray presented by the measured liver tissue. The optimized algorithm had a sensitivity ranging from 0.81 to 0.83, with a specificity of 0.95 for differentiation of hepatic tumors from normal tissues. We obtained a 96% agreement between the pixels segmented by an experienced radiologist and the algorithm presented here. According to the results shown in this work, the algorithm is optimal for the beginning of the tests for quantification of liver tumors in retrospective surveys.

Neste trabalho, é apresentada uma metodologia original, baseada na transformada de wavelet, de segmentação de tumores hepáticos. Foi construído um fantoma virtual com mesma média e desvio padrão de intensidade de cinza do apresentado pelos tecidos hepáticos medidos. O algoritmo otimizado apresentou uma sensibilidade variando de 0,81 a 0,83 , com uma especificidade de 0,95 para a diferenciação de tumores hepáticos de tecidos normais. Foi obtida uma concordância de 96% entre os pixels segmentados por um radiologista experiente e o algoritmo aqui apresentado. Pelos resultados demonstrados neste trabalho, o algoritmo encontra-se em fase ótima para começar os testes de quantificação de tumores hepáticos em exames retrospectivos.
Wavelets in quantification of liver tumors in contrasted computed tomography images
Keywords: Liver diseases; Tomography; X-ray; Wavelet analysis; Hepatopatias; Tomografia por raios X; Análise de ondaletas